Epidemiology of injury in elite English schoolboy rugby union: A 3-year study comparing different competitions - Barden, C.; Stokes, K. (Journal of Athletic Training, 2018)
Context: Injury risks in professional and community rugby union have been extensively described; however, less is known about injury epidemiology at the schoolboy level.